Adaptação marginal de cimentos à base de silicato de cálcio à parede dentinária de cavidades retrógadas - Renovato, Sara Rodrigues (2019)
Objective: To analyse the marginal adaptation of calcium silicate-based cements in root-end cavity by SEM. Material and Methods: Fifty bovine roots were prepared with K-File #60 and filled with gutta-percha and MTA Fillapex. Roots were apicetomized and a 3-mm-deep root-end cavity was prepared using ultrasonic tips. Samples were randomly divided into five groups (n = 10): 1. Mk Life bioceramic cement; 2. Biodentine®; 3. Bio-C Repair®; 4. Endosequence® BC RRM™; 5. MTA Angelus® (MTA) - positive control. Root-end cavities were filled with the materials prepared according to the manufacturers’ instructions. EDTA was used prior the retro-filling material insertion in half of the samples from each group (n = 5). Samples were prepared for SEM and photomicrographs were taked in x40, x150 and x500. The images of root-end fillings were divided into four áreas and distributed into five scores: 0 - absence of gaps; 1 - presence of gap in 1 area; 2 - presence of gap in 2 areas; 3 - presence of gap in 3 areas; 4 - presence of gaps in 4 areas. The analysis of transverse dimension of the gap (μm) was performed using Image J software. Qualitative variables were evaluated by Fisher Exact Test and quantitative variables by Analysis of Variance (ANOVA) . The level of significance was 0.05%. Results: No gaps were observed in MTA Angelus® group (0%). Presence of gaps were observed in Mk Life bioceramic cement (90%), Biodentine® (80%), Bio-C Repair® (100%) and Endosequence® BC RRM™ (80%). Significant difference was observed when MTA were compared to Mk Life bioceramic cement, Biodentine®, Bio-C Repair® and Endosequence® BC RRM™ (p <0.05). No significant difference were observed in the transverse dimension of the gap between Mk Life bioceramic cement, Biodentine®, Bio-C Repair® and Endosequence® BC RRM™ groups. MTA show significantly better result than Mk Life bioceramic cement and Bio-C Repair® groups (p <0.05), but without significant difference with Biodentine® and Endosequence® BC RRM™ Conclusion: MTA Angelus® showed better marginal adaptation compared to MK Life bioceramic cement, Biodentine® , BioC Repair® and Endosequence® BC RRM™. Marginal gaps were not observed in samples of MTA Angelus® group.